Analysis of Health Benefits Associated with Exclusive Breastfeeding Among Lactating Mothers in Maiduguri Metropolis, Borno State, Nigeria for Sustainable National Development - Idris Alhaji Haruna (International Journal of Women's Health Nursing And Practices, 2025)
Exclusive breastfeeding, which involves feeding an infant only breast milk for the first 6 months of life, offers numerous health benefits for both the baby and the breastfeeding mother. Despite the well-established advantages, global rates of exclusive breastfeeding remain lower than ideal, and this is also the case in Maiduguri Metropolis, Borno State, Nigeria. This study aims to explore the health benefits of exclusive breastfeeding for lactating mothers in Maiduguri Metropolis. A total of 150 mothers who have given birth to live infants under 6 months old were selected as participants using purposive and simple random sampling methods for the research. The primary data were obtained using structured questionnaire that wereadministered to 150 lactating mothers in the study area while secondary information was obtained from journals, textbooks, internet, conference papers, etc. The analytical tools that were employed for this study include descriptive statistics and 5-point Likert-type scale. A study investigating the health benefits associated with exclusive breastfeeding among lactating mothers is expected to yield compelling results, shedding light on the positive impacts of this practice on maternal and infant health outcomes.
Keywords: Breastfeeding; Health Benefits; breastfeeding mother; infant; lactating mothers